Plasma Cathepsin D Activity Rather Than Levels Correlates With Metabolic Parameters of Type 2 Diabetes in Male Individuals - Ding, Lingling; Houben, Tom; Oligschlaeger, Yvonne; Bitorina, Albert V.; Verwer, Bart J.; Tushuizen, Maarten E.; Shiri-Sverdlov, Ronit (Frontiers in Endocrinology, 2020)
Abstract Objective: Type 2 diabetes mellitus is a metabolic disorder characterized by insulin resistance. Previous studies in patients demonstrated that plasma levels of cathepsin D (CTSD), which is optimally active in the acidic environment of lysosomes, correlate with insulin resistance. As plasma pH is slightly reduced in type 2 diabetic patients and we have previously shown that plasma CTSD activity is causally linked to insulin levels in vivo, it is likely that the activity of CTSD in plasma will be increased in type 2 diabetes compared to healthy individuals. However, so far the interaction between CTSD activity and levels to postprandial metabolic derangements in type 2 diabetes is not known. Methods: Eighteen type 2 diabetes and 16 age-matched healthy males were given 2 consecutive standardized mixed meals, after which blood samples were collected. Plasma metabolic parameters as well as CTSD levels and activity were measured, and changes in plasma pH was assessed. Results: In line with the elevation of plasma free fatty acids (FFA) levels in male type 2 diabetics patients, plasma pH in type 2 diabetic individuals was decreased compared to male healthy individuals. While plasma CTSD levels were similar, plasma CTSD activity was increased in male type 2 diabetic compared to male healthy individuals. Besides, plasma CTSD activity rather than levels significantly correlated with indicators of type 2 diabetes (HbA1c, HOMA-IR and glucose). Furthermore, FFA was also independently associated with plasma CTSD activity (standardized β=0.493, p=0.007). Conclusions: Despite similar plasma CTSD levels between healthy and type 2 diabetic male individuals, the metabolically-induced reduction of plasma pH in male type 2 diabetic individuals results in increased plasma CTSD activity which in return links to elevated plasma lipid and glucose levels. Our data therefore point towards plasma CTSD as a metabolic regulator in male type 2 diabetes.